Care coordination in adult social care: Exploring service characteristics within the non-statutory sector in England. (September 2018) - Sutcliffe, Caroline; Jasper, Rowan; Hughes, Jane; Abendstern, Michele; Challis, David
Summary: As a result of national policy in respect of social care of adults in England, the non-statutory sector is increasingly more evident in the provision of care services previously undertaken by local government, including the delivery of care coordination for older people. However, little is currently known about the scope, content, or quality of services providing care coordination within this sector. This article reports the findings from a postal survey undertaken in January 2014 of non-statutory organisations in England providing care coordination services and investigates variations in their key attributes. Organisations providing care coordination services were identified using various strategies to create a database of services. Questionnaires encompassing several areas of enquiry were mailed to managers of care coordination services identified from the database. Findings: There was similarity in the operation of the care coordination services sampled. Many were small-scale services, contract-funded, and providing short-term support. Volunteer staff were a feature of most services. All services worked to written protocols and standards and almost all levied no charge. Many shared information with healthcare or local authority staff with user consent. Service user satisfaction was measured and used for service improvement. Application: This is one of the first studies undertaken in England to investigate the provision of care coordination by the non-statutory sector and to identify patterns of variation in key service attributes. Implications for commissioners, service providers, workforce, and social workers are further discussed. The findings provide baseline data against which future developments can be measured.